2020
DOI: 10.1021/acs.jafc.9b06898
|View full text |Cite
|
Sign up to set email alerts
|

3,4-seco-Dammarane Triterpenoid Saponins with Anti-Inflammatory Activity Isolated from the Leaves of Cyclocarya paliurus

Abstract: Cyclocarya paliurus is commonly used for the prevention and treatment of hypertension, diabetes, and inflammation in South China. Although research on the anti-inflammatory effects of C. paliurus leaves has been reported, no active anti-inflammatory compounds have been identified. In the present study, RAW 264.7 cells were used to establish a bioactivity-guided identification model to verify the inhibitory effects of C. paliurus leaves on inflammation and identify the anti-inflammatory constituents. The active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Modern pharmacological studies have found that many potential bioactive compounds (triterpenoids, polysaccharides, flavonoids, etc.) in the leaves of C. paliurus have beneficial effects on antihypertensive activity, hypoglycemic activity, hypolipidemic activity, and antioxidant activity [ 10 ]. Due to the lack of breakthroughs in its asexual reproduction technology, sexual reproduction is still the main means of reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies have found that many potential bioactive compounds (triterpenoids, polysaccharides, flavonoids, etc.) in the leaves of C. paliurus have beneficial effects on antihypertensive activity, hypoglycemic activity, hypolipidemic activity, and antioxidant activity [ 10 ]. Due to the lack of breakthroughs in its asexual reproduction technology, sexual reproduction is still the main means of reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…is suggests that the saponins in the methanol root extract of M. triphylla could be responsible for the better potency of the methanol extract in inhibiting inflammation in comparison to the aqueous extract [45].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 29 compounds were identified, including 3 phenolic acids, 10 flavonoids, and 16 triterpenoids (Table 1). These compounds were 3-O-caffeoylquinic acid, 4-O-caffeoylquinic acid, catechin, isoquercetin, quercetin-3-Oglucuronide, kaempferol-3-O-galactoside, kaempferol-3-O-glucuronide, kaempferol-3-Oglucoside, quercetin-3-O-rhamnoside, myricetin, kaempferol-3-O-rhamnoside, quercetin, kaempferol, 3β,19α,23-trihydroxy-1-oxo-olean-12-en-28-oic acid, arjunolic acid, cyclocaric acid B, asiatic acid, pterocaryoside B, cyclocarioside I, cyclocarioside K, pterocaryoside A, cyclocariol C, (20S,24R)-20,24-epoxy-25-hydroxy-12β-(α-L-arabinopyranosyloxy)-3,4-secodammara-4-( 28)-en-3-oic acid, cyclocarioside B, hederagenin, cyclocarioside H, cyclocarioside X, cypaliuruside E, and ursolic acid [17,[30][31][32][33][34][35][36][37][38][39][40].…”
Section: Characterization Of Chemical Constituents In Cpe Cpf Cpp and Cptmentioning
confidence: 99%
“…A total of 29 compounds were identified, including 3 phenolic acids, 10 flavonoids, and 16 triterpenoids (Table 1). These compounds seco-dammara-4-( 28)-en-3-oic acid, cyclocarioside B, hederagenin, cyclocarioside H, cyclocarioside X, cypaliuruside E, and ursolic acid [17,[30][31][32][33][34][35][36][37][38][39][40].…”
Section: Characterization Of Chemical Constituents In Cpe Cpf Cpp and Cptmentioning
confidence: 99%